1995
DOI: 10.1007/bf00181866
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic dural ectasia mimicking neurofibroma and scoliosis

Abstract: Angular thoracic scoliosis combined with dural ectasia and foraminal enlargement is reported in a patient with neurofibromatosis. The dural cyst was resected through a high thoracic approach and the scoliosis dealt with by posterior spinal fixation with Modulock instrumentation. Follow up after 12 months showed no neurological deficit and no progress of the scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…To the best of our knowledge, only seven patients with similar dural cysts have been reported in the literature, and these are summarized in Table 1. 1,2,5,8,10 A similar dural cyst of the cerebellum has been reported in a 9-month-old boy. 7 Whereas the intracranial dura mater can be separated into two distinct layers with a potential epidural space, the spinal dura represents a downward extension of the inner layer of the cerebral dura.…”
Section: Discussionsupporting
confidence: 58%
“…To the best of our knowledge, only seven patients with similar dural cysts have been reported in the literature, and these are summarized in Table 1. 1,2,5,8,10 A similar dural cyst of the cerebellum has been reported in a 9-month-old boy. 7 Whereas the intracranial dura mater can be separated into two distinct layers with a potential epidural space, the spinal dura represents a downward extension of the inner layer of the cerebral dura.…”
Section: Discussionsupporting
confidence: 58%
“…Successful posterior fusion with little progression of dural ectasia and spinal deformities, as observed in our case, has been reported [9]. The progression of dural ectasia and bone erosion despite surgical treatment has also been documented [6].…”
Section: Discussionsupporting
confidence: 52%
“…Earlier studies have reported various treatments for spinal deformities in the thoracic or lumbar spine [6][7][8][9][10][11][12][13], but reports pertaining to cervical spine deformities have been rare [14,15]. Furthermore, few studies have assessed the long-term follow-up findings of dural ectasia postoperatively.…”
Section: Introductionmentioning
confidence: 96%
“…[ 21 35 ] On the other hand, dural ectasia has been reported after trauma and after spinal surgery[ 21 36 ] as well. In additional, the pathology can also occur at cervical[ 37 ] or thoracic levels[ 38 ] without lumbar involvement. Curiously, our patient had no history of connective tissue disorder, and no signs/symptoms to suggest an undiagnosed disorder.…”
Section: Discussionmentioning
confidence: 99%